ANALISIS YURIDIS TINDAK PIDANA PENGGABUNGAN HUKUM PIDANA KASUS BIBI RANDIKA (Studi Kasus Putusan Mahkamah Agung Nomor 520 K/Pid.Sus/2016): (Studi Kasus Putusan Mahkamah Agung Nomor 520 K/Pid.Sus/2016) - Br Sinaga, Sara Clara Hagata (Universitas Harapan Medan, 2024)
Combined criminal offenses are often termed concursus or samenloop. Combination of criminal offenses is the occurrence of two or more criminal offenses by one person where the first criminal offense has not been sentenced, or between the first criminal offense and the next criminal offense has not been limited by a decision. The writing of this thesis uses a library research method to examine secondary data by analyzing the case of Supreme Court Decision Number 520 K/Pid.Sus/2016. This type of research data is secondary data. Primary and secondary legal materials are arranged systematically and analyzed qualitatively. From the results of the research, it is concluded that if a person commits more than one criminal act, only one act can be sentenced, namely the act with the most severe legal threat among other acts. The form of criminal sanction given to the perpetrator of the merger of criminal acts (samenloop van strafbepalingen) in Supreme Court Decision Number 520 K/Pid.Sus/2016 is that the defendant is sentenced to imprisonment for 18 (eighteen) years, and a fine of Rp. 25,000,000.00 (twenty-five million rupiah). Consideration of the combination of criminal offenses (samenloop van strafbepalingen.